University and Community Collaboration in Empowering the Local Economy through Entrepreneurship and Digital Marketing Training for MSMEs and the Outer Baduy Community - Mawardi, Amna; Jaya, Umban Adi; Hodijah, Cucu; Winarni, Riani (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2025)
Backgrounds: The limited access to markets, technology, and business development opportunities has become one of the key challenges hindering the economic growth of the Outer Baduy community and local MSMEs. Objectives: This community service activity aims to empower micro, small, and medium enterprises (MSMEs) and the Outer Baduy community through entrepreneurship and digital marketing training. Methodology: The program was implemented collaboratively by universities and involved 30 participants, consisting of youth, craft workers, and tourism stakeholders. Implementation methods included entrepreneurial motivation, social media-based digital marketing training, and hands-on practice in creating promotional content for local products. Findings: Results showed that 66.7% of participants were able to create digital business accounts, 50% successfully produced simple promotional content, and the majority began to understand the importance of innovation and digital market access. The resulting impacts included increased digital literacy, entrepreneurial knowledge, collaborative networks, and a shift in mindset toward technology. Conclusions: Thus, this program has proven effective as an initial model for local economic empowerment based on university collaboration that is inclusive, adaptive, and aligned with the cultural wisdom of the Outer Baduy community.